The Influence of Microstructure and Softening Characteristics of Zinc-Lead Sinter on the Operation of an Imperial Smelting Furnace - Shoobridge PH; Firkin GR (The Australasian Institute of Mining and Metallurgy, 1980)
The Imperial Smelting Process blast furnace (ISF) of the Sulphide Corporation Pty Limited zinc/lead smelter at Cockle Creek, New South wales, has in recent years greatly increased its consumption of low grade feed materials, and as a consequence has experienced periods of unstable furnace operation. Routine examination of production sinter, including softening characteristics and micro- examination, showed that the problems had been caused by an increasing silica content in sinter. The silica entered a low melting point glass phase containing calcium and lead oxides. The relative volume of this phase increased until it formed a continuous matrix in the sinter structure and this made the sinter more likely to soften at lower temperatures. Premature softening caused loss of operating stability in both the shaft and hearth of the ISr. The required sinter structure for ISF smelting was found to consist of a network of intermeshing, refractory crystals which provided skeletal strength for sinter lumps even after the glass phases had begun to soften and melt. With an understanding of the importance of microstructure and softening temperature of zinc/lead sinter and the progressive identification of those factors in sinter production which affect the microstructure, a significant improvement in stability of operations has been possible.